“Give Her the Baby’s Hat so She Can Bite it”: Obstetric Violence in Flores, Indonesia - Alicia Paramita Rebuelta-Cho (Université de Provence, 2021)
The medicalization of birth is bringing about precipitous changes in local birth-giving practices in the Sikka district (Flores, Indonesia), particularly with the prohibition of homebirths in 2009. However, homebirths remain a concern for biomedical professionals, who suspect that some women still give birth at home for reasons they do not want to disclose. This paper shows that even though women do express the desire to give birth in medical facilities and expect to benefit from a combination of biomedical and local treatments, this is made impossible by different forms of obstetric violence within the labour wards, which include: the long-time exposure of genitals, the imposition of the supine position, the systematic use of episiotomy, painful stitching and the absence of local practices such as being supported by a du’a rawin (healer), pulling on a rope during contractions, or waiting a few minutes before cutting the umbilical cord. As a consequence, while some women choose to receive treatment in medical facilities, others prefer to empower themselves and give birth in an environment of cultural safety.